Dialektika Relasional dalam Proses Pemulihan Hubungan Pasca Keretakan Rumah Tangga Akibat Perselingkuhan di Tempat Kerja - Jevica Tifany; Muhamad Isnaini; Teguh Hidayatul Rachmad (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
Marital breakdown due to infidelity is a social phenomenon that affects the quality of a couple's relationship and the psychological well-being of the family. This study aims to understand the process of relationship recovery after infidelity using relational dialectics theory. The research subjects consisted of four married couples living in Tambora, West Jakarta, who experienced marital conflict due to infidelity in the workplace. The approach used was descriptive qualitative with an intrinsic case study method. Data were obtained through in-depth interviews with the couples, participatory observation in their daily lives, and documentation related to the experiences and recovery processes undergone by the couples. The results of the study show that relationship recovery is greatly influenced by how couples manage relational tensions such as openness vs. privacy, stability vs. change, connection vs. autonomy, and expression vs. silence. Couples who successfully rebuild trust tend to practice open and empathetic communication and allow space for individual needs. Conversely, couples who fail to maintain their relationship exhibit limited communication and resistance to change. These findings emphasize the importance of communication in the process of relationship recovery after a crisis, as well as reinforcing the relevance of relational dialectics theory in understanding the dynamics of couple conflict.Keretakan rumah tangga akibat perselingkuhan menjadi fenomena sosial yang berdampak pada kualitas hubungan pasangan dan kesejahteraan psikologis keluarga. Penelitian ini bertujuan untuk memahami proses pemulihan hubungan pasca perselingkuhan dengan menggunakan teori dialektika relasional. Subjek penelitian terdiri dari empat pasangan suami istri yang tinggal di Tambora, Jakarta Barat, yang mengalami konflik rumah tangga akibat perselingkuhan di tempat kerja. Pendekatan yang digunakan adalah kualitatif deskriptif dengan metode studi kasus intrinsik. Data diperoleh melalui wawancara mendalam dengan pasangan, observasi partisipatif dalam kehidupan sehari-hari mereka, serta dokumentasi terkait pengalaman dan proses pemulihan yang dilalui pasangan-pasangan tersebut. Hasil penelitian menunjukkan bahwa pemulihan hubungan sangat dipengaruhi oleh cara pasangan mengelola ketegangan relasional seperti keterbukaan vs privasi, stabilitas vs perubahan, koneksi vs otonomi, dan ekspresi vs keheningan. Pasangan yang berhasil membangun kembali kepercayaan cenderung menerapkan komunikasi terbuka dan empatik, serta memberikan ruang bagi kebutuhan individu. Sebaliknya, pasangan yang gagal mempertahankan hubungan menunjukkan komunikasi terbatas dan penolakan terhadap perubahan. Temuan ini menegaskan pentingnya komunikasi dalam proses pemulihan hubungan setelah krisis, serta memperkuat relevansi teori dialektika relasional dalam memahami dinamika konflik pasangan.